Nanomechanics - Vakhrushev, Alexander (IntechOpen, 2017)
In recent years, nanotechnology is the basis for the development of modern production. This determined the urgency of the intensive development of the new direction of mechanics and nanomechanics, for the scientific description of nanotechnological processes and the solution of several topical nanotechnology problems. Topics included in the book cover a wide range of research in the field of nanomechanics: thermomass theory of nanosystems; deformation of nanomaterials; interface mechanics of assembly carbon nanotube; nanomechanics on surface; molecular interactions and transformations; nanomechanical sensors, nanobeams, and micromembranes; nanostructural organic and inorganic materials; green synthesis of metallic nanoparticles. The main goal of these works is the establishment of the nanosystem macroparameter dependence on its nanoparameters using nanomechanics. This book will be useful for engineers, technologists, and researchers interested in methods of nanomechanics and in advanced nanomaterials with complex behavior and their applications.